Hybrid Literacy Instruction Method for Children with Intellectual Disabilities - AKÇİN, FATMA NUR (ANKARA UNIV, FAC EDUCATIONAL SCIENCES, 2019)
Due to the lack of a separate literacy instruction method for students with intellectual disabilities, existing methods for typically developing children are mostly used as they are, or sometimes with modifications and adaptations. These methods can be used with various instructional adaptations, for children with mild intellectual disabilities, whereas it is not possible to use them as effectively for children with moderate-to-severe intellectual disabilities due to their cognitive and learning characteristics. While the goal is only to acquire functional reading for children with severe intellectual disabilities, it goes as far as academic literacy for children with moderate intellectual disabilities. The hybrid literacy instruction method was developed by scanning and compiling the results of scientific research in the field of literacy instruction for children with intellectual disabilities. This method comprises of hierarchical stages such as sight word instruction, letter knowledge instruction, monosyllabic word reading instruction, and multisyllabic word reading instruction. Due to the integrated use of three separate strategies, namely the sight word reading strategy, analytical phonic strategy and analogy strategy, it is a hybrid/mixed instructional method.
Keywords: Intellectual disability; development of literacy learning; literacy instruction method; word reading strategies; hybrid method; WORD RECOGNITION; READING-SKILLS; DOWN-SYNDROME; STUDENTS; ACQUISITION; KINDERGARTEN; INDIVIDUALS; COMPREHENSION; FOUNDATIONS; STRATEGIES